1995
DOI: 10.2337/diab.44.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Athletes With IDDM Exhibit Impaired Metabolic Control and Increased Lipid utilization With No Increase in Insulin Sensitivity

Abstract: Physical exercise is traditionally recommended to diabetic patients as part of their treatment. Although healthy athletes exhibit enhanced skeletal muscle insulin sensitivity, the metabolic effects of vigorous training in patients with insulin-dependent diabetes mellitus (IDDM) are not known. This study was designed to examine the effects of competitive sports on fuel homeostasis and insulin sensitivity in athletes with IDDM. We studied 11 athletes and 12 matched sedentary men with IDDM. In each subject, we me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 28 publications
1
15
1
Order By: Relevance
“…Daily insulin requirement was also reduced. This finding is in good agreement with former exercise studies in patients with type 1 diabetes (34). Experimental studies demonstrated exercise-increased expression and function of several proteins involved in insulin-signal transduction (35).…”
Section: Fuchsjä Ger-mayrl and Associatessupporting
confidence: 81%
“…Daily insulin requirement was also reduced. This finding is in good agreement with former exercise studies in patients with type 1 diabetes (34). Experimental studies demonstrated exercise-increased expression and function of several proteins involved in insulin-signal transduction (35).…”
Section: Fuchsjä Ger-mayrl and Associatessupporting
confidence: 81%
“…Diabetic men may tend to decrease insulin doses to prevent hypoglycemic periods during or after high-intensity physical activity, thus avoiding hypoglycemic symptoms but at the same time losing any possible positive effect of physical activity on glycemic control. This statement is merely speculative and based on our cross-sectional data but is supported by data on male athletes with type 1 diabetes showing poor glycemic control despite high physical activity (32). In our study, however, no association between HbA 1c and LTPA in men was found despite adjustment for insulin dose.…”
Section: Research Design Andcontrasting
confidence: 45%
“…Fasting plasma glucose concentration was determined using glucose oxidase method (Beckman glucose analyzer, Beckman Instruments, Fullerton, Calif., USA). Serum C peptide, total and HDL-cholesterol and triglyceride concentrations were determined as described previously [16]. Haemoglobin A 1c (reference range 4.0±6.0 %) at baseline (n = 21) and at the end of the treatment (n = 26) were determined with a DCA 2000 analyser (Bayer Diagnostics).…”
Section: Methodsmentioning
confidence: 99%